50 anos de renovação da Igreja na América Latina: aprendizados da história - Passos, João Décio (Revista Eclesiástica Brasileira, 2019)
A reflexão apresenta os pontos principais do processo de renovação eclesial ocorrido na América Latina, segundo a pauta do aggiornamento conciliar. Expõe os tópicos centrais dessa renovação e o decorrente arrefecimento que vai sofrendo no decorrer do tempo. Afirma a necessidade de que toda reforma atinja a esfera estrutural da instituição para que possa sobreviver historicamente com seus princípios e pautas. Afirma também a validade emblemática do carisma renovador da Igreja dos pobres, demarcado na Conferência de Medellín, para os dias de hoje, tanto nas Igrejas do continente, quanto para as reformas colocadas em marcha pelo Papa Francisco no conjunto da Igreja. Abstract: The reflection presents the main points of the process of ecclesial renewal that took place in Latin America, according to the agenda of the conciliar aggiornamento. It exposes the central topics of this renewal and the resulting cooling that will suffer over time. It affirms the need for any reform to reach the structural sphere of the institution so that it can survive historically with its principles and guidelines. It also affirms the emblematic validity of the renewing charism of the Church of the poor, set out in the Medellin Conference, for the present day, both in the Churches of the continent and in the reforms proposed by Pope Francisco in the Church as a whole. Keywords: Latin America; Francis; Church; The Poor and Ecclesial Reform.